1999
DOI: 10.1001/jama.282.8.755
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders Among Survivors of the Oklahoma City Bombing

Abstract: Our data suggest that a focus on avoidance and numbing symptoms could have provided an effective screening procedure for PTSD and could have identified most psychiatric cases early in the acute postdisaster period. Psychiatric comorbidity further identified those with functional disability and treatment need. The nearly universal yet distressing intrusive reexperience and hyperarousal symptoms in the majority of nonpsychiatrically ill persons may be addressed by nonmedical interventions of reassurance and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
492
4
20

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 803 publications
(566 citation statements)
references
References 23 publications
(30 reference statements)
50
492
4
20
Order By: Relevance
“…These findings are consistent with earlier reports surrounding the survivors of other disasters such as the Oklahoma City bombing, wherein it was reported that 45% of the subjects had a post-disaster psychiatric illness and 34.3% had PTSD. 6 In contrast, in Israel, a constant threat of war and exposure to terrorism resulted in PTSD in 9.4% of residents, which was similar to that found after September 11 among New York residents. 1,7,8 However, the rate of PTSD in Israel is lower than the rates of PTSD reported for persons in the immediate vicinity of the WTC within 2 months after the September 11 attack.…”
Section: Discussionsupporting
confidence: 55%
“…These findings are consistent with earlier reports surrounding the survivors of other disasters such as the Oklahoma City bombing, wherein it was reported that 45% of the subjects had a post-disaster psychiatric illness and 34.3% had PTSD. 6 In contrast, in Israel, a constant threat of war and exposure to terrorism resulted in PTSD in 9.4% of residents, which was similar to that found after September 11 among New York residents. 1,7,8 However, the rate of PTSD in Israel is lower than the rates of PTSD reported for persons in the immediate vicinity of the WTC within 2 months after the September 11 attack.…”
Section: Discussionsupporting
confidence: 55%
“…Many of the samples studied have been small and not representative of the affected community's population (Bromet & Dew, 1995). For example, North et al (1999) used a confidential registry of survivors from the Oklahoma City Bombing. Even though the sample was representative of the registry, the authors note that it overrepresented individuals who were close to the blast and was, therefore, not representative of Oklahoma City's population.…”
Section: Introductionmentioning
confidence: 99%
“…North et al, (1999) reported that those directly exposed to a mass disaster have a prevalence rate of 34% for a potential PTSD diagnosis. Six months after the Alfred Murrah Federal Building bombing in Oklahoma City, 45% of the survivors reported mental health needs, with 34% displaying PTSD (North et al, 1999). In spite of variations in the statistical data, all studies indicated that direct exposure to a traumatic event greatly increased the chances of developing PTSD.…”
Section: Ptsd Prevalence Statisticsmentioning
confidence: 99%